Secretory System Components as Potential Prophylactic Targets for Bacterial Pathogens - Wieslaw Swietnicki (Biomolecules, 2021)
Bacterial secretory systems are essential for virulence in human pathogens. The systems have become a target of alternative antibacterial strategies based on small molecules and antibodies. Strategies to use components of the systems to design prophylactics have been less publicized despite vaccines being the preferred solution to dealing with bacterial infections. In the current review, strategies to design vaccines against selected pathogens are presented and connected to the biology of the system. The examples are given for Y. pestis, S. enterica, B. anthracis, S. flexneri, and other human pathogens, and discussed in terms of effectiveness and long-term protection.